Acidic ambiance induced post-oxidative stress aﬀects AMPK- PGC1α-SIRT1 axis in the skeletal muscles of zebraﬁsh Danio rerio Hamilton, 1822 - Chowdhury, Sabarna; Chatterjee, Subhendu K.; Bhattacharya, Samir; Maitra, Sudipta; Saikia, Surjya K. (Acta Biologica Szegediensis, 2021)
The present study was aimed to understand whether acidic pH induces oxidative stress in zebrafish affecting metabolic sensor protein and thereby, the mitochondrial functions in the skeletal muscle of zebrafish. The experiments performed in aquaria involved the study of the changes of HIF1α, AMPK, PGC1α and SIRT1 levels together with the levels of mitochondrial Tfam and Nrf1. The results obtained from investigation of superoxide dismutase (SOD), catalase and glutathione revealed that the fish undergoes oxidative stress within a short duration of exposure to acidic ambiance. Further analysis with MDA and HIF1α helped to understand the effects of post oxidative stress on skeletal muscle of the fish at pH 5.0 (± 0.5). Of the three tissues studied (gill, brain and skeletal muscle) the effect was maximum in skeletal muscle as depicted by MDA level at 2 hours beyond which it declines augmenting death or mortality (15%) to the fish. Consequently, HIF1α was increased as an adaptive strategy against metabolic disruption during the first 2 hours period. However, on exposure to pH 5.0 (± 0.5) for 2 hours, there were decrease of the metabolic sensors viz. AMPK and SIRT1 followed by mitochondrial gene transcriptional co-activator PGC1α. The expression of mitochon-drial transcription factors Tfam and Nrf1 were also reduced confirming perturbation in mitochondrial function affecting low ATP production compared to control. This was also supported by the decrease of COXII as well as mitochondrial complex I activity. All these results confirm that the metabolic machinery of zebrafish is affected when pH was lowered to 5.0 (± 0.5).